A Perfusion Bioreactor Model of Tumor‐Induced Bone Disease Using Human Cells. Issue 1 (5th January 2022) - Lowen, Gregory B.; Vanderburgh, Joseph P.; Florian, David; Scott, Taylor; Sterling, Julie A. Rhoades; Guelcher, Scott A.
Abstract: Advanced solid tumors often metastasize to bone. Once established in bone, these tumors can induce bone destruction resulting in decreased quality of life and increased mortality. Neither 2D in vitro models nor 3D animal models sufficiently recapitulate the human bone‐tumor microenvironment needed to fully understand the complexities of bone metastasis, highlighting the need for new models. A 3D in vitro humanized model of tumor‐induced bone disease was developed by dynamically culturing human osteoblast, osteoclast, and metastatic cancer cells together within tissue‐engineered bone constructs. Cell‐mediated resorption can be observed by micro‐computed tomography and can be quantified by change in mass. Taken together, these data can be used to investigate whether the metastatic cancer cells included in the model have the potential to drive osteoclastogenesis and cell‐mediated resorption in vitro . © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Fabricating bone‐like scaffolds Basic Protocol 2 : Preparing cells for the humanized model of TIBD Basic Protocol 3 : Crafting a 3D in vitro humanized model of TIBD